Cost‐Effectiveness of the Early Arthritis Clinic Organizational Model. Issue 5 (5th December 2022) - Zanetti, Anna; Sakellariou, Garifallia; Zambon, Antonella; Carrara, Greta; Argnani, Lisa; Mantovani, Lorenzo G.; Cortesi, Paolo A.; Bugatti, Serena; Montecucco, Carlomaurizio; Scirè, Carlo A.
Abstract : Objective: Early diagnosis and tight control improve outcomes of rheumatoid arthritis (RA). However, whether establishing an early arthritis clinic (EAC) is sustainable for national health systems is not known. This analysis aimed to compare effectiveness and costs of an EAC compared to patients followed by the current standard of care. Methods: A retrospective study on administrative health databases of patients with a new diagnosis of RA was conducted: 430 patients followed in an EAC were enrolled, and 4 non‐EAC controls were randomly matched for each. During 2 years of follow‐up, the mean health care costs (outpatient, inpatient, pharmaceutical, and global) and 3 effectiveness measures (number and length of hospitalization and quality of care) of the EAC and non‐EAC were estimated. The incremental cost‐effectiveness ratio was calculated as well as the cost‐effectiveness acceptability curve. Results: The cohorts included patients with a mean age of 55.4 years, and 1, 506 patients (70%) were female. The mean pharmaceutical (2, 602 versus 1, 945 euros) and outpatient (2, 447 versus 1, 778 euros) costs were higher in the EAC cohort. Conversely, a higher rate of non‐EAC patients had a low adherence to quality‐of‐care indicators. The expected number of hospitalizations and the length of stay were statistically significantly higher in the non‐EAC versus EAC. Conclusion: Despite an expected increase in outpatient costs (visits and diagnostic tests) and pharmaceutical costs, the reduction in terms of number and length of hospitalizations and the higher adherence to international quality‐of‐care guidelines support the effectiveness of the EAC model.